2021
DOI: 10.1101/2021.03.25.437033
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neural speech tracking shifts from the syllabic to the modulation rate of speech as intelligibility decreases

Abstract: The most prominent acoustic features in speech are intensity modulations, represented by the amplitude envelope of speech. Synchronization of neural activity with these modulations is vital for speech comprehension. As the acoustic modulation of speech is related to the production of syllables, investigations of neural speech tracking rarely distinguish between lower-level acoustic (envelope modulation) and higher-level linguistic (syllable rate) information. Here we manipulated speech intelligibility using no… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 58 publications
7
15
0
Order By: Relevance
“…These values parallel theoretical considerations and neurophysiological observations (Giraud & Poeppel, 2012;Giroud et al, 2020) and provide a behavioral validation that phonemic sampling occurs at such a rate (see also (Marchesotti et al, 2020). While the acoustic modulation and syllabic rates are often reduced to one another, they are dissociable (see also (Schmidt et al, 2021), are associated with different processing bottlenecks, but both unfold at around 5 Hz in natural speech and have a channel capacity of around 15 Hz. This result strongly suggests that both low-level acoustic and language-specific rhythmic processes contribute to speech comprehension.…”
Section: Discussionsupporting
confidence: 67%
“…These values parallel theoretical considerations and neurophysiological observations (Giraud & Poeppel, 2012;Giroud et al, 2020) and provide a behavioral validation that phonemic sampling occurs at such a rate (see also (Marchesotti et al, 2020). While the acoustic modulation and syllabic rates are often reduced to one another, they are dissociable (see also (Schmidt et al, 2021), are associated with different processing bottlenecks, but both unfold at around 5 Hz in natural speech and have a channel capacity of around 15 Hz. This result strongly suggests that both low-level acoustic and language-specific rhythmic processes contribute to speech comprehension.…”
Section: Discussionsupporting
confidence: 67%
“…The envelope modulation rate of the 24 audio files in the original, 7-ch, 5-ch, 3-ch, 2-ch, and 1-ch vocoded condition was 5.61 Hz, 5.53 Hz, 5.27 Hz, 5.23 Hz, 4.93 Hz, and 4.83 Hz, respectively. A main effect of vocoding was observed [ 𝒳 2 (5) = 206.0, p = 1.83 × 10 −42 , Kendall’s W = 0.134, Friedman test], in line with Schmidt et al (2021).…”
Section: Methodssupporting
confidence: 56%
“…Late responses around 315-380 ms (M350 TRF ) were strongest at medium vocoding levels as compared to clear and less intelligible speech. To complement our findings in TRF, we also computed speech envelope reconstruction, speech-brain coherence, and periodic components (peak center frequency, peak bandwidth, peak height) and aperiodic components (exponent, offset) of broadband coherence spectra (Schmidt et al, 2021). Relating the TRF components to those neural measures, we found that M50 TRF and M200 TRF were correlated with the center frequency of the broadband coherence spectra in a different direction.…”
Section: Introductionmentioning
confidence: 97%
“…Our findings show, for the first time, that the tendency to anticipate low-level acoustic features according to their contextual probability facilitates the cortical tracking of the speech envelope. Tracking of information conveyed by the speech envelope is critical for speech comprehension and the processing of low-level linguistic features (Schmidt et al, 2021; Vanthornhout et al, 2018). This suggests a potentially supportive role of the tendency to anticipate low-level acoustic features on the processing of naturally spoken language.…”
Section: Discussionmentioning
confidence: 99%